Analisis Break Even Point Penambangan Sirtu PT. Klawafun Alam Lestari Papua Barat - Fernando Nanlohy; Juanita R. Horman (JFRES Journal of Fiscal and Regional Economy Studies, 2019)
This study aims to analyze Break Even Point of mining of sirtu at PT. Klawafun Alam Lestari Provinsi Papua Barat. The method used in this research is quantitative method. Break Even Point shows the point where income is equal to cost. Intended costs are variable costs and fixed costs. Where fixed costs consist of capital costs and labor costs, while variable costs consist of production costs. From the results of data collection and calculation, the fixed cost is Rp. 9,501,158,600 and variable cost of Rp. 48,972/m3, at the selling price of sirtu Rp. 150.000/m³. From the analysis, Break Even Point of mining of sirtu is obtained when the minimum mining production reaches 94,045 m³/year with an income of Rp. 14,106,720,810.07/year.